STILL - Yeng, Desree Wei Si (Nanyang Technological University, 2022)
Tenacity and drive – Traits that Singaporean women boxers possess. Sabrina, Leona and Danisha fight tirelessly for their sport. But a personal drive to succeed can only get you so far in the face of institutional inequality and neglect. Instead of backing down, they punch back stronger and harder. STILL follows these Singaporean women as they push against the glass ceiling that boxed them in.